ELEVATED PRE-TREATMENT NEUTROPHIL-TO-LYMPHOCYTE AND NEUTROPHIL-TO-LYMPHOCYTE-PLATELET RATIOS ARE ASSOCIATED WITH A HIGH RISK OF IN-HOSPITAL DEATH AMONG PATIENTS WITH PROSTATE CANCER IN SOUTHEASTERN NIGERIA (Journal of Biomedical Investigation, 2023)
Background: There is an increasing mortality rate among patients diagnosed with prostate cancer (PCa) in West Africa. To identify the causes of the high mortality rate, this study analyzed the occurrence of high-grade tumours and presence of BRCA2 gene loss. It also assessed the utility of systemic inflammatory indices as prognostic tools in low-resource settings.Methods: This study included 72 cases of PCa diagnosed from Jan. 2017 to Dec. 2020. The neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelets- neutrophils-to-lymphocytes ratio (PNLR), and neutrophils-to-lymphocytes platelets ratio (NLPR) were assessed and analyzed accordingly. Significance was set at p< 0.05.Results: The prevalence of Gleason grades (G) 1 to 5 was 9.3%, 16.3%, 16.3%, 25.6, and 32.6%, respectively. There was a high frequency of BRCA2 loss (58.3%) and frequency was higher among patients with G4/5 tumours (59.5%) than in patients with G1-G3 tumours (46.7%) at p= 0.347. A high frequency of G4/5 tumours was observed among patients within the age group of 50-59 years (n= 7/8; 87.5%) and patients with castration-resistant PCa (n= 12/17; 70.6%). The pre-treatment PLR and calcium concentration were higher among patients with G4/5 tumours compared to patients with G1-G3 tumours (p= 0.046 and < 0.001, respectively.) There were direct relationships between BRCA2 expression and age (p= 0.019), tumour grade and calcium (p= 0.000), BRCA2 and calcium expression (p= 0.027), unemployment and G4/5 (p< 0.001), and education status and G4/5 (p= 0.020). The pre-treatment NLR and NLPR were 2.0 and 4.7 times higher in in-hospital deaths than in stable discharges at p= 0.005 and 0.001, respectively.Conclusion: This study revealed high frequencies of BRCA2 loss and high-grade PCa in Southeastern Nigeria. It also revealed elevated pre-treatment NLR and NLPR in cases of in-hospital death. It suggests that pre-treatment PLR could be used to identify patients with G4/5.
Keywords: Systemic inflammation; Gleason grade; castration-resistant; calcium; BRCA2 mutation